Bronchoscopy findings in 1074 lung cancer patients in a tertiary care center in Nepal - Shrestha, Shashank; Thakur, Binay; Devkota, Mukti; Bhandari, Nikesh; Kharel, Ashish; Thapa, Asha (Nepalese Journal of Cancer, 2022)
Background: Fiberoptic bronchoscopy is the most important diagnostic tool for lung cancer. Early tissue diagnosis and proper staging remains the key to the management of the lung cancer patient. Endobronchial forceps biopsy has high diagnostic yield from the visible lesions. The aim of the study was to evaluate diagnostic yield of endobronchial biopsy.Methods: A retrospective cross-sectional study was conducted at B.P. Koirala Memorial Cancer Hospital, Bharatpur, Nepal. Bronchoscopy reports of 1074 patients from January 2000 to December 2009 were included. Endobronchial biopsy was the main procedure performed.Results: A total of 1074 patients underwent bronchoscopy for suspected lung cancer. Majority of the patients (N=340) had lesion in lobar bronchus. Squamous cell carcinoma was the most common histological diagnosis. The diagnostic yield of endobronchial biopsy was 75%. The diagnostic yield for central tumor was 82.3% which was statistically significant (p